Bukalapak Online Store's SWOT-Based Service Quality Improvement Strategy - Shadli Rolaskhi (Universitas Kristen Indonesia Toraja, 2022)
The purpose of this research is to be able to analyze the strengths, weaknesses, opportunities and threats of using the Bukalapak online store. The research conducted is qualitative in nature. As for collecting data using questionnaires. As for the data processing technique used is to use the SWOT method. Population determination involves internal and external parties. The technique used is to use the SWOT method. Where internal parties involve admin sellers who have direct access to consumers while external parties are students who are in the Palembang city area. The results of the study show that from the internal side it is at coordinates 0.54, while in the factor matrix while on the external side it is at coordinates 0.37. So from the internal matrix mapping and external matrix it shows that Bukalapak is still in a strong position and still has business opportunities.